Estimation of Carbon Content in Mangrove Stands in The Santong Bay Mangrove Ecotourism Area Sumbawa Regency - Safitri, Desti Suci; Latifah, Sitti; Valentino, Niechi (Jurnal Biologi Tropis, 2024)
This study aims to analyze the vegetation composition, estimate biomass content, and examine carbon storage in mangrove stands in the Mangrove Ecotourism Area of Teluk Santong. The research employs a descriptive method to provide insights into natural phenomena or community relations by studying existing issues based on collected data, which is then processed through data presentation, analysis, and drawing conclusions. *Rhizophora apiculata* species dominate the mangrove area, with the highest Importance Value Index (IVI) for tree level reaching 365.50%. The estimated carbon stored in the mangrove stands is 3.07 tons/ha, with a biomass of 6.53 tons/ha and carbon dioxide storage of 76.52 tonsCO₂/ha. Carbon storage in a particular mangrove species increases with the growth in individual tree diameter. *Rhizophora apiculata* has higher density, diameter, and biomass values than *Avicennia alba*. Additionally, the CO₂ absorption capacity of *Rhizophora apiculata* is much higher than that of *Avicennia alba*, reaching 69 tons CO₂/ha.